Doing philosophy with a water-lance: art and the future of embodied cognition. (December 2022) - Feiten, Tim Elmo; Holland, Kristopher; Chemero, Anthony
We take the approach developed by Rietveld and RAAAF to be a paradigm example of a much-needed development in embodied cognitive science: applying the insights gained into the nature of cognition back to embodied cognition itself, back to the practice of bodily engagements with our sociocultural environments. Rietveld's work is groundbreaking precisely because it stands almost alone as a prototype of this move: to raise embodiment from a mere content of our theorizing to the practical level of determining the form of our activity, including our scholarly activity. We describe some of our own artistic-scholarly work that follows similar principles.